2018 IEEE Global Engineering Education Conference (EDUCON) 2018
DOI: 10.1109/educon.2018.8363340
|View full text |Cite
|
Sign up to set email alerts
|

MOOC dropout prediction using machine learning techniques: Review and research challenges

Abstract: MOOC represents an ultimate way to deliver educational content in higher education settings by providing high-quality educational material to the students throughout the world. Considering the differences between traditional learning paradigm and MOOCs, a new research agenda focusing on predicting and explaining dropout of students and low completion rates in MOOCs has emerged. However, due to different problem specifications and evaluation metrics, performing a comparative analysis of state-of-the-art machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(90 citation statements)
references
References 27 publications
(34 reference statements)
1
72
0
2
Order By: Relevance
“…Whitehill et al (2015) design an online intervention strategy to boost users' callback in MOOCs. Dalipi et al (2018) review the techniques of dropout prediction and propose several insightful suggestions for this task. What's more, XuetangX has organized the KDDCUP 2015 2 for dropout prediction.…”
Section: Related Workmentioning
confidence: 99%
“…Whitehill et al (2015) design an online intervention strategy to boost users' callback in MOOCs. Dalipi et al (2018) review the techniques of dropout prediction and propose several insightful suggestions for this task. What's more, XuetangX has organized the KDDCUP 2015 2 for dropout prediction.…”
Section: Related Workmentioning
confidence: 99%
“…In this section, we will briefly discuss the studies related to MOOC dropout prediction. Dalipi et al [6] performed a survey of studies conducted for MOOC dropout prediction. They observed that different research groups tended to choose different data sources and extract different features.…”
Section: Related Workmentioning
confidence: 99%
“…However, this process is difficult because of several reasons. First, the MOOC learners may drop out for different reasons [6] . Some learners may only attempt to experience MOOC as a new type of learning.…”
Section: Introductionmentioning
confidence: 99%
“…However, such studies as [4], [5] note that the new learning technology faces such challenges as low completion and retention rates, certification, graduation, and verification of student's identity, and unsuitability for complex and engineering education. Nevertheless, this process continues expanding despite declining educational attainment in these spheres [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many research papers are devoted to the exploration of motives that drive students to enrol in one or another e-course and the reasons of their failure. In [4], lack of student's motivations is identified as an influential factor in preventing Electrical, Control and Communication Engineering ________________________________________________________________________________________2019, vol. 15, no.…”
Section: Introductionmentioning
confidence: 99%